28 days : a novel of resistance in the Warsaw Ghetto - Safier, David 1966- (Feiwel and Friends, 2020)
Zusammenfassung: In Warsaw, Poland, in 1942, Mira faces impossible decisions after learning that the Warsaw ghetto is to be "liquidated," but a group of young people are planning an uprising against their Nazi captors.